Peran Pembelajaran Pantun dalam Penguatan Karakter Santun Era Digital - Andayani, Ruli; Mardiyana, Indra (Kajian Bahasa dan Sastra (KABASTRA), 2024)
Pantun is a classic work of Indonesian literature that still exists today. The didactic values contained in it are still relevant to the times, especially as a strengthening of polite character for the younger generation. As an adaptation and modernization effort, pantun learning can be done by utilizing technology. This research aims to describe (1) the value of polite character in pantun and (2) the form of digital-based pantun learning. The research was conducted descriptively-qualitatively. Data collection was done through observation, interview, and literature study. The research data is in the form of verbal information about pantun obtained from literature review, as well as observation and interview notes. The results showed that through pantun, students can communicate politely, namely when greeting, conveying motivational messages, and giving advice or suggestions among peers. Students showed high enthusiasm when participating in digital-based pantun learning. All students were able to write and display their works according to the stimulus given by the teacher.